Light-controlled switching of the spin state of iron(III). Issue 1 (December 2018) - Shankar, Sreejith; Peters, Morten; Steinborn, Kim; Krahwinkel, Bahne; Sönnichsen, Frank; Grote, Dirk; Sander, Wolfram; Lohmiller, Thomas; Rüdiger, Olaf; Herges, Rainer
Abstract Controlled switching of the spin state of transition metal ions, particularly of FeII and FeIII, is a prerequisite to achieve selectivity, efficiency, and catalysis in a number of metalloenzymes. Here we report on an iron(III) porphyrin with a photochromic axial ligand which, upon irradiation with two different wavelengths reversibly switches its spin state between low-spin (S  = 1 /2 ) and high-spin (S  = 5 /2 ) in solution (DMSO-acetone, 2:598). The switching efficiency is 76% at room temperature. The system is neither oxygen nor water sensitive, and no fatigue was observed after more than 1000 switching cycles. Concomitant with the spin-flip is a change in redox potential by ~60 mV. Besides serving as a simple model for the first step of the cytochrome P450 catalytic cycle, the spin switch can be used to switch the spin-lattice relaxation timeT 1 of the water protons by a factor of 15. Controlled switching of the spin state of transition metal ions is key in many enzymatic reactions, but difficult to replicate in synthetic systems. Here the authors report on an iron(III) porphyrin with a photochromic axial ligand that, in solution, reversibly switches between low-spin and high-spin upon irradiation with two different wavelengths.